Water conflict among sectors and environmental uses in Jordan - Shatanawi M.; Shammout M.; Naber S. (Water culture and water conflict in the Mediterranean area, 2008)
In Jordan, access to scarce water resources is a common cause of conflict and there is a continuing competition between sectors about the use of water. This complex interaction is leading inexorably to internal water conflict that inspiring the need of solutions over water use and availability. As such, increasing demand has been a constant concern for Jordanian's leaders because surface, groundwater reservoirs are under stress, and the need of several sectors to use limited water supplies; nevertheless, the subsistence of other water resources and instruments aid to overcome the conflict between sectors. Like other conflicts that revolve around limited water resources, identifying the water issues will guide to the different possible alternatives. The objective of this paper is to summarize the current problems regarding water shortages, supplies, and demand for Jordan including the relationship between the available water resources and the conflict between different sectors. The effective management, development, water allocation, monitoring, and policies can potentially reduce water conflict between sectors.
1. MELIA Workshop Water Culture and Water Conflict, 2007/11/22-25, Nabeul-Médenine (Tunisia)